Analysis of The Effect of Economic Growth, Energy Consumption and Economic Openness on Carbon Emissions (CO2) in Indonesia - Saputra, Hendri Andika; Hidayat, Paidi; Tanjung, Ahmad Albar (Ekonomis: Journal of Economics and Business, 2025)
The purpose of this study is to analyze the influence of economic growth, energy consumption, and economic openness on carbon dioxide (CO2) emissions in Indonesia. This study uses the ARDL (Autoregressive Distributed Lag) method and the Granger Causality test. The results reveal that economic growth has a positive and significant effect on carbon emissions in the long term, but does not have a significant effect in the short term. Meanwhile, energy consumption has a positive and significant effect on carbon emissions in both the short and long term. On the other hand, economic openness has a negative effect on carbon emissions, but the effect is not significant in both the short and long term. The findings of this study indicate that Indonesia is at the Environmental Kuznets Curve (EKC) stage, with a turning point in economic growth of 6.61%. Initially, economic growth increases CO2 emissions, but after reaching this turning point, economic growth begins to have a positive effect on improving environmental quality. In addition, this study also found a reciprocal relationship between economic openness and carbon emissions.